A PFC3D-based numerical simulation of cutting load for lunar rock simulant and experimental validation. Issue 10 (15th May 2017) - Li, Peng; Jiang, Shengyuan; Tang, Dewei; Xu, Bo
Abstract: For sake of striking a balance between the need of drilling efficiency and the constrains of power budget on the moon, the penetrations per revolution of drill bit are generally limited in the range around 0.1 mm, and besides the geometric angle of the cutting blade need to be well designed. This paper introduces a simulation approach based on PFC 3D (particle flow code 3 dimensions) for analyzing the cutting load feature on lunar rock simulant, which is derived from different geometric-angle blades with a small cutting depth. The mean values of the cutting force of five blades in the survey region (four on the boundary points and one on the center point) are selected as the macroscopic responses of model. The method of experimental design which includes Plackett-Burman (PB) design and central composite design (CCD) method is adopted in the matching procedure of microparameters in PFC model. Using the optimization method of enumeration, the optimum set of microparameters is acquired. Then, the experimental validation is implemented by using other twenty-five blades with different geometric angles, and the results from both simulations and laboratory tests give fair agreements. Additionally, the rock breaking process cut by different blades are quantified from simulation analysis. This research provides the theoretical support for the refinement of the rock cutting load prediction and the geometric design of cutting blade on the drill bit.